Limited and biased global conservation funding means most threatened species remain unsupported - Benoit Guénard; Alice C. Hughes; Claudianne Lainé; Stefano Cannicci; Bayden D. Russell; Gray A. Williams (Proceedings of the National Academy of Sciences, 2025)
The conservation of biodiversity represents a global challenge as the world experiences its sixth mass extinction. Understanding how conservation efforts are allocated is paramount to effectively protect threatened species. We analyzed ~14,600 conservation projects over a 25-y period, revealing substantial taxonomic biases in funding. When matched with formal assessments of species’ threat status, several highly threatened groups such as amphibians receive little and ever-decreasing support. Within particular groups (e.g., Mammalia, Reptilia), funding is directed to a very narrow selection of taxa, leaving the majority of their threatened species with limited or no support. More attention is urgently needed to assess the extinction risks of neglected taxa, especially smaller species. Paradoxically, while approximately 6% of species identified as threatened were supported by conservation funds, 29% of the funding was allocated to species of “least concern”. A more holistic distribution of conservation funding is, therefore, urgently needed if we are to protect biodiversity efficiently. We suggest avenues and mechanisms for a more balanced coverage of threatened species within conservation programs and highlight some of the benefits that could be derived from such an approach.